Influence of COVID‐19 pandemic on molar pregnancy and postmolar gestational trophoblastic neoplasia: An observational study. (21st October 2022) - Campos, Vanessa; Paiva, Gabriela; Padron, Lilian; Freitas, Fernanda; Pedrotti, Luana Giongo; Sun, Sue Yazaki; Viggiano, Maurício; Oliveira, Larissa; Rohr, Lucia; Madi, José Mauro; Arrym, Tiago Pedromônico; Oliveira, Priscila; et al.
Abstract: Objective: To assess whether the incidence and aggressiveness of molar pregnancy (MP) and postmolar gestational trophoblastic neoplasia (GTN) changed during the COVID‐19 pandemic. Design: Observational study with two separate designs: retrospective multicentre cohort of patients with MP/postmolar GTN and a cross‐sectional analysis, with application of a questionnaire. Setting: Six Brazilian Reference Centres on gestational trophoblastic disease. Population: 2662 patients with MP/postmolar GTN treated from March–December/2015–2020 were retrospectively evaluated and 528 of these patients answered a questionnaire. Methods: Longitudinal retrospective multicentre study of patients diagnosed with MP/ postmolar GTN at presentation and a cross‐sectional analysis, with application of a questionnaire, exclusive to patients treated during the period of study, to assess living and health conditions during the COVID‐19 pandemic compared with previous years. Main outcome measures: The incidence of MP/postmolar GTN. Results: Compared with the last 5 pre‐pandemic years, MP/postmolar GTN incidence remained stable during 2020 (COVID‐19 pandemic). Multivariable logistic regression, adjusted for the patient age, showed that during 2020, presentation with MP was more likely to be >10 weeks of gestation (adjusted odds ratio [aOR] 2.50, 95% confidence interval [CI] 1.90–3.29, P < 0.001), have a pre‐evacuation hCG level ≥100 000 iu/l (aOR 1.77, 95% CI 1.38–2.28, P < 0.001) and time to the initiation of chemotherapy ≥7 months (aOR 1.86, 95% CI 1.01–3.43, P = 0.047) when compared with 2015–2019. Conclusions: Although the incidence of MP/postmolar GTN remained stable during the COVID‐19 pandemic in Brazil, the pandemic was associated with greater gestational age at MP diagnosis and more protracted delays in initiation of chemotherapy for postmolar GTN.